2017
DOI: 10.1002/adem.201700264
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Stages during Ultrasonic Processing that Reduce the Grain Size of Aluminum with Added Al3Ti1B Master Alloy

Abstract: The combined application of UST and Al3Ti1B grain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…One of these is ultrasonic vibration or what will henceforth be called Ultrasonic Treatment (UST). It is a mechano‐physical process characterized in this context by low‐amplitude and high‐intensity, where extensive research has shown UST to effectively refine the as‐cast grain structure without using inoculant particles . In fact, one could surmise from this research that UST has considerable potential as a clean, versatile, and efficient technology.…”
Section: Introductionmentioning
confidence: 92%
“…One of these is ultrasonic vibration or what will henceforth be called Ultrasonic Treatment (UST). It is a mechano‐physical process characterized in this context by low‐amplitude and high‐intensity, where extensive research has shown UST to effectively refine the as‐cast grain structure without using inoculant particles . In fact, one could surmise from this research that UST has considerable potential as a clean, versatile, and efficient technology.…”
Section: Introductionmentioning
confidence: 92%
“…The liquid treatment, UST-L, produces excellent refinement when the alloy contains more potent substrates and solute (Atamanenko et al, 2010;Wang et al, 2017c;Nagasivamuni et al, 2019a). The solidification treatment UST-S, on the other hand, can produce refinement in pure metals (Wang et al, 2017d;Nagasivamuni et al, 2018) and dilute alloys (Wang et al, 2014(Wang et al, , 2016a(Wang et al, , 2017bSrivastava et al, 2017) without potent substrates.…”
Section: Discussionmentioning
confidence: 99%
“…During the stage 2, below the liquidus temperature, the nucleation of grains will be enhanced by cavitation, which may also promote the breakage and detachment of grains formed on the ultrasonic generator. In addition to transmitting the grains, the acoustic streaming also produces a uniform undercooling temperature in the melt [34], thereby ensuring the survival of these new grains and producing a uniform fine grain size throughout the composites ingot. figure 7.…”
Section: The Refinement Grain Size Of Composites Under the Magnetic Amentioning
confidence: 99%